PENGARUH ONLINE CONSUMER REVIEW DAN RATING TERHADAP KEPERCAYAAN KOSUMEN DAN KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DI KOTA PEKABARU - Danty Sukma Nabillah; Jushermi Jushermi; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Abstract-This study aims to determine the Online Consumer Reviews and Ratings on Consumer Trust and Purchase Decisions at Shopee E-commerce in Pekanbaru City. The population in this study are consumers who have shopped online at Shopee e-commerce who are domiciled in Pekanbaru City whose number is not known with certainty. Premiere data were collected using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study was to use the path analysis method (path analysis) with the help of the SPSS program. The sampling technique chosen was snowball sampling (105 people at Shopee site customers in Pekanbaru City).The results showed that:1) Online Consumer Review has a positive and significant effect on Consumer Trust in Shopee E-commerce in Pekanbaru City, 2) Rating has a positive and significant effect on Consumer Trust in Shopee E-commerce in Pekanbaru City, 3) Online Cosumer Review has a positive and significant effect on Purchasing Decisions at Shopee E-commerce in Pekanbaru City, 4) Rating has a positive and significant effect on Purchasing Decisions at Shopee E-commerce in Pekanbaru City, 5) Consumer Trust has a positive and significant effect on Purchasing Decisions in E-commerce Shopee in Pekanbaru City, 6) Online Consumer Review has a positive and significant effect on Purchasing Decisions through Consumer Trust in Shopee E-commerce in Pekanbaru City, 7) Rating has a positive and significant effect on Purchasing Decisions through Consumer Trust in Shopee E-commerce in Pekanbaru City.Keywords: Online Consumer Review, Rating, Consumer Confidence and Purchasing Decisions